Feasibility and efficiency of double-agent versus single-agent concurrent chemoradiotherapy in patients with nasopharyngeal carcinoma. (July 2020) - Qin, Guanjie; Rai, Raju; Zhang, Rongjun; Su, Yixin; Zhang, Bin; Pan, Yuefei; Xiong, Ruihua; Xie, Yuan; Yang, Huiyun; Kong, Xiangyun; Luo, Zan; Ruan, Xiaolan; et al.
Highlights: Multivariate analysis showed that CCRT regimen had no significant effects on survival. d-CCRT regimen did not confer significant survival benefits in the treatment of stage II-IV NPC patients. Patients treated with the d-CCRT regimen experienced greater hematological toxicity. Abstract: Purpose: Concurrent chemoradiotherapy (CCRT) is the mainstay of treatment for nasopharyngeal carcinoma (NPC) patients. It remains unclear whether double-agent CCRT (d-CCRT) is more effective than single-agent CCRT (s-CCRT). In this study, we compared the treatment efficiency and toxicity of d-CCRT with s-CCRT in NPC patients. Methods and materials: Patients with stage II-IV NPC treated with d-CCRT or s-CCRT were retrospectively reviewed. The d-CCRT group patients were compared with s-CCRT group patients for overall survival (OS), locoregional relapse-free survival (LRRFS), disease-free survival (DFS), distant metastasis-free survival (DMFS) and toxicity. Differences in baseline characteristics were adjusted using the pair-matching method. Results: In this study, 933 patients who received CCRT for NPC between 2011 and 2014 were pair-matched at a 1:2 ratio (n = 311 for d-CCRT; n = 622 for s-CCRT). The d-CCRT treated patients showed no significant advantages in terms of 4-year OS (87.2% vs. 85.5%), DFS (84.1% vs. 79.5%), LRRFS (94.6% vs. 91.8%), DMFS (87.5% vs. 85.5%) compared with s-CCRT treated patients ( P  = 0.450, 0.106, 0.203, 0.366, respectively). Multivariate analysis showed that CCRT regimen had no significant effects on survival. In the d-CCRT group, the incidence of grade 3–4 hematological toxicities was significantly higher. Conclusions: The d-CCRT regimen did not confer significant survival benefits compared with the s-CCRT regimen in the treatment of stage II-IV NPC patients. Furthermore, patients treated with the d-CCRT regimen experienced greater hematological toxicity.